The membrane-associated β2e-subunit of voltage-gated calcium channels translocates to the nucleus and regulates gene expression - Erick Miranda-Laferte; Katalin Barkovits; Katalin Barkovits; Svitlana Rozanova; Svitlana Rozanova; Nadine Jordan; Katrin Marcus; Katrin Marcus; Patricia Hidalgo; Patricia Hidalgo (Frontiers in Physiology)
The β-subunit (Cavβ) is a central component of the voltage-gated calcium channel complex. It lacks transmembrane domains and exhibits both channel-related and non-related functions. Previous studies have shown that, in the absence of the Cavα1 pore-forming subunit, electrostatic interactions between the N-terminus of Cavβ2e and the plasma membrane mediate its anchoring to the cell surface. Here, we demonstrate that, upon phospholipase C activation, Cavβ2e dissociates from the plasma membrane and homogeneously distributes between the cytosol and the nucleus. Mutagenesis analysis identified critical residues in the N-terminus of the protein, including a stretch of positively charged amino acids and a dileucine motif, which serve as nuclear import and export signals, respectively. Fusion of the Cavβ2e N-terminus to a trimeric YFP chimeric construct shows that this segment suffices for nuclear shuttling. Thus, the N-terminus of Cavβ2e emerges as a regulatory hotspot region controlling the subcellular localization of the protein. Quantitative mass spectrometry analysis revealed that the heterologous expression of a nuclear-enriched Cavβ2e mutant regulates gene expression. Our findings demonstrate the presence of active nuclear localization signals in Cavβ2e that enables its nuclear targeting and regulation of protein expression. Furthermore, they establish the membrane-associated Cavβ2e as a novel signaling mediator within the phospholipase C cascade.